2022
DOI: 10.31219/osf.io/5e4sa
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

“I felt like I deserved it because I was Autistic”: Understanding the Impact of Interpersonal Victimisation in the Lives of Autistic People

Abstract: Research suggests that there is a high prevalence of interpersonal violence and victimisation within the autistic population, and that this accounts for poor mental health outcomes. This study aimed to examine the impact of interpersonal victimisation on autistic adults from their own perspective, and explore what helps or hinders their recovery. One hundred and two autistic adults completed either an online survey, or a spoken interview about their experiences of interpersonal victimisation. We analysed the d… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…These highly distressing experiences often occurred in the school context, where being seen as different elicited adverse reactions from peers (Boyle, 2021;Humphrey & Lewis, 2008). Over time, driven by concerns for safety and survival, autistic people developed camouflaging strategies to protect themselves against future victimization Cage & Troxell-Whitman, 2019;Chapman et al, 2022;Hull et al, 2017;Kofke, 2019;Loo et al, 2021;Pearson et al, 2022). With camouflaging, participants felt less vulnerable and more confident and secure Cage & Troxell-Whitman, 2019); it not only gave them a respite from bullying but also protected them from the emotional and mental repercussions of being victimized (Chapman et al, 2022).…”
Section: Overview Of Findingsmentioning
confidence: 99%
See 3 more Smart Citations
“…These highly distressing experiences often occurred in the school context, where being seen as different elicited adverse reactions from peers (Boyle, 2021;Humphrey & Lewis, 2008). Over time, driven by concerns for safety and survival, autistic people developed camouflaging strategies to protect themselves against future victimization Cage & Troxell-Whitman, 2019;Chapman et al, 2022;Hull et al, 2017;Kofke, 2019;Loo et al, 2021;Pearson et al, 2022). With camouflaging, participants felt less vulnerable and more confident and secure Cage & Troxell-Whitman, 2019); it not only gave them a respite from bullying but also protected them from the emotional and mental repercussions of being victimized (Chapman et al, 2022).…”
Section: Overview Of Findingsmentioning
confidence: 99%
“…Clinical psychologists observed that autistic girls tend to camouflage more than boys due to a greater desire to identify with a social group (Muggleton et al, 2019). Autistic individuals often camouflaged to fit in and belong, be liked by others, and form friendships and romantic connections (Cook et al, 2018;Cook, Crane, et al, 2021;Hull et al, 2017;Milner et al, 2019;Myles et al, 2019;Myles, 2017;Pearson et al, 2022;Samoilis, 2021). Having previously faced rejection for their autistic differences, they felt that they could not be accepted as their autistic selves and thus strived to minimize the visibility of their differences by camouflaging Hickey et al, 2018;Loo et al, 2021).…”
Section: Subtheme 22 "I Thought That [Masking]mentioning
confidence: 99%
See 2 more Smart Citations